STRATEGY FOR DEVELOPING STUDENTS' MULTICULTURAL COMPETENCY THROUGH RELATIONAL CULTURAL THERAPY TRAINING - Lesmana, Gusman; Wastuti, Sri Ngayomi Yudha; Deliati, Deliati (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2024)
This study aims to measure the effectiveness of relational cultural therapy in improving the multicultural competence of students specifically in guidance and counseling study program students as prospective BK/counselor teachers who will provide services to clients who have different cultural backgrounds. This study uses a quantitative type with a pretest-posttest group design. The subjects of this study were 40 students at FKIP UMSU who needed to receive the latest training on multicultural competence. The analysis used was product moment correlation and produced a correlation coefficient of 0.981 which concluded that rational cultural therapy training provided a significant increase in students' multicultural competence